PENTINGNYA MANAJEMEN STRATEGIS KEPALA SEKOLAH DALAM PEMBELAJARAN DARING DI PUSAT KEGIATAN BELAJAR MASYARAKAT [THE IMPORTANCE OF THE PRINCIPAL’S STRATEGIC MANAGEMENT IN ONLINE LEARNING AT PUSAT KEGIATAN BELAJAR MASYARAKAT] - Lenny Lenny (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
During the COVID-19 pandemic situation, one of the most affected sectors is education. Distance learning become the only possible way to execute the learning process for both formal and nonformal education institutes. The principal is the key to success of the progress and continuity of their organization. By being able to identify the problems that the organization is facing, the principal is responsible for formulating strategic steps and then implement those steps. The role of the principal really matters. The purpose of this research is to evaluate the role of the principal in implementing the strategic management during online learning. This is an evaluative study using qualitative research method. The data is collected through deep interviews with the source person and continuous observation done by the writer. In this research, the writer concludes that the role of the principal at PKBM XYZ is important. She and her team have implemented the strategic steps that they formulated together. Therefore, the online learning process may run effectively and efficient for the students. Nevertheless, by implementing those strategic steps, she has created a comfortable work situation for the staff. The obstacles occurred during the implementation process are basically technical issues and can be solved. The evaluation result from this implementation conclude that the principal will keep putting her best effort to maximize her role as leader.